Development of Ag/GO Incorporated onto PES Membrane with Improved Anti-Fouling Property - Vatsha, Banele; Ngila, Jane C.; Moutloali, Richard (Journal of Membrane and Separation Technology, 2015)
Graphene and its derivatives have got increasingly application interests emanating from its unique properties. This work reports silver-graphene oxide sheets (Ag-GO) composite synthesis and then incorporated into Polyethersulfone (PES) casting solution. The composite casting mixtures were cast via phase inversion method. Graphene and its derivatives were characterised by ATR/FTIR, Raman, XRD and TEM. The morphology and performance of the neat PES and composite PES membranes were characterised by SEM, AFM, CA, permeation flux, protein (BSA) rejection, antifouling and antibacterial tests. The composite membranes exhibited a slightly higher permeation flux and then gradual decreased compared to neat PES membranes. However, the antifouling tests revealed that the composite membranes with Ag particles showed a preferable antifouling performance. The antibacterial tests confirmed that the composite membranes exhibited a effective antibacterial performance against both gram-positive (E. coli) and gram-negative (S. Aureus) strains.